2020
DOI: 10.1037/law0000220
|View full text |Cite
|
Sign up to set email alerts
|

Your bias is rubbing off on me: The impact of pretrial publicity and jury type on guilt decisions, trial evidence interpretation, and impression formation.

Abstract: Pretrial publicity (PTP) can bias jurors' decisions. The courts often assume such bias can be ameliorated or reduced by jury deliberations. This study explored the effects of PTP (antiprosecution, antidefense, or no-PTP) and jury type (pure vs. mixed) on mock-jurors'/juries' (N ϭ 495/96) verdicts, impressions, and trial evidence interpretation. PTP affected predeliberation verdicts, with antidefendant PTP jurors being the most likely to render guilty verdicts, and antiprosecution PTP jurors the least likely. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Taken together, the findings above suggest that the makeup of the jury influenced the interpretation of trial evidence and how it was discussed during deliberations. This finding is consistent with past research measuring jurors' interpretation of trial evidence as a function of PTP exposure (Ruva & Coy, 2020;Ruva & Guenther, 2017), as well as research examining predecisional distortion (Hope et al, 2004;Ruva et al, 2011). Specifically, pure NV juries had a bias toward discussing trial facts with a prodefense slant, whereas pure ND juries had a bias toward discussing trial facts with a proprosecution slant.…”
Section: H2: Slant Of Trial Fact Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Taken together, the findings above suggest that the makeup of the jury influenced the interpretation of trial evidence and how it was discussed during deliberations. This finding is consistent with past research measuring jurors' interpretation of trial evidence as a function of PTP exposure (Ruva & Coy, 2020;Ruva & Guenther, 2017), as well as research examining predecisional distortion (Hope et al, 2004;Ruva et al, 2011). Specifically, pure NV juries had a bias toward discussing trial facts with a prodefense slant, whereas pure ND juries had a bias toward discussing trial facts with a proprosecution slant.…”
Section: H2: Slant Of Trial Fact Discussionsupporting
confidence: 89%
“…As noted above, both ND PTP and NV PTP have been found to influence jurors' interpretation of trial evidence (Hope et al, 2004;Ruva & Coy, 2020;Ruva & Guenther, 2017). Importantly, research has found that mock-jurors' discussion and evaluation of trial evidence during deliberations is influenced by PTP exposure (Ruva & Guenther, 2015;Ruva & LeVasseur, 2012).…”
Section: Story Modelmentioning
confidence: 89%
See 1 more Smart Citation
“…Future research is necessary to determine whether the effect size created from rich, nonprobative information is greater than the small effects Another way to mix probative information with nonprobative information would be to use a pre-trial publicity paradigm. Information from media sources outside the trial has been shown to be confused by mock-jurors for evidence admitted at trial, and when this information was negative, it has been shown to lower the perceived credibility of the accused (Ruva & Coy, 2020;Ruva, McEvoy, & Bryant, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Another way to mix probative information with nonprobative information would be to use a pre‐trial publicity paradigm. Information from media sources outside the trial has been shown to be confused by mock‐jurors for evidence admitted at trial, and when this information was negative, it has been shown to lower the perceived credibility of the accused (Ruva & Coy, 2020; Ruva, McEvoy, & Bryant, 2007). Future research could examine the impact of nonprobative and probative pre‐trial publicity (including, but not limited to nonprobative photos), and the resulting impact on perceived credibility.…”
Section: Discussionmentioning
confidence: 99%